A Microring Temperature Sensor Based on the Surface Plasmon Wave. (15th February 2015) - Li, Wenchao; Sha, Xiaopeng; An, Dongyang; Li, Zhiquan
Abstract : A structure of microring sensor suitable for temperature measurement based on the surface plasmon wave is put forward in this paper. The sensor uses surface plasmon multilayer waveguiding structure in the vertical direction and U-shaped microring structure in the horizontal direction and utilizes SOI as the thermal material. The transfer function derivation of the structure of surface plasmon microring sensor is according to the transfer matrix method. While the change of refractive index of Si is caused by the change of ambient temperature, the effective refractive index of the multilayer waveguiding structure is changed, resulting in the drifting of the sensor output spectrum. This paper focuses on the transmission characteristics of multilayer waveguide structure and the impact on the output spectrum caused by refractive index changes in temperature parts. According to the calculation and simulation, the transmission performance of the structure is stable and the sensitivity is good. The resonance wavelength shift can reach 0.007 μ m when the temperature is increased by 100 k and FSR can reach about 60 nm. This structure achieves a high sensitivity in the temperature sense taking into account a wide range of filter frequency selections, providing a theoretical basis for the preparation of microoptics.